(untitled) (Fountain Journal of Natural and Applied Sciences, 2018)
The antidiarrhoeal potentials of ethanolic extract of Aristolochia ringens stem back was evaluated in castor oil-induced diarrhoeal rats. The A. ringens stem back ethanolic extract was, in addition, screened for its phytoconstituents. Thirty albino rats of 150-180 g were randomized into six groups of five animals each for each of the three experiments and all administration were oral. Rats in groups I and II were administered 1.0 ml distilled water and 1% DMSO (Vehicle) respectively, while those in group III were administered 2.5 mg/kg b.wt loperamide hydrochloride as reference drug. Rats in groups IV, V and VI were administered 25, 50, and 100 mg/kg b.wt. ethanolic extract of A. ringens stem bark. The castor oil-induced diarrhoeal model was used, the weight and volume of the intestinal content was determined by enteropooling method and the intestinal motility was determined using activated charcoal method. The small intestine of the rats was also assessed for histopathological changes. The extract significantly and dose-dependently reduced the number of diarrhoeal faeces, the volume of intestinal accumulation and the distance moved by the fed charcoal in treated rats compared to the untreated diarrhoeal group (group II). The percentage inhibitions exhibited by the extract at 50 and 100 mg/kg body weight were significantly higher than that of the reference drug. Furthermore, the photomicrograph of the intestine of the extract treated rats showed intact intestinal architecture. Hence, ethanolic extract of Aristolochia ringens stem bark may contain phytochemicals with better antidiarrhoeal potentials which can be explored in the development of more viable antidiarrhoeal agents. Keywords: Aristolochia ringens, Antidiarrhoeal agents, Intestinal motility, Intestinal accumulation